Global frequency, diagnosis, and treatment of hereditary angioedema with normal C1 inhibitor - Markus Magerl, MD; Marc A. Riedl, MD, MS; Luisa Karla Arruda, MD, PhD; Andrea Bauer, MD, MPH; Alejandro Berardi, MD; Jonathan A. Bernstein, MD; Laurence Bouillet, MD, PhD; Matthew Buckland, PhD; Thomas Buttgereit, MD; Danny M. Cohn, MD, PhD; Timothy Craig, DO; Roberta F. Criado, MD, PhD; et al. (Journal of Allergy and Clinical Immunology: Global)
Background: Hereditary angioedema (HAE) is a rare genetic disease, most frequently associated with deficiency or dysfunction in the C1 inhibitor protein. HAE with normal C1 inhibitor (HAE-nC1INH) lacks standardized diagnostic tests, limiting precise prevalence estimates and development of specific treatment guidelines. Objective: This study sought to describe the global frequency, diagnostic pathway, and current treatment patterns of HAE-nC1INH. Methods: Board-certified HAE-treating physicians from accredited Angioedema Centers of Reference and Excellence (ACAREs) were invited to complete a 27-item online survey between December 2022 and April 2023. Results: Thirty physicians from 30 ACAREs across 15 countries reported a mean of 71 (range, 11-148) patients with HAE assessed/treated within the previous 12 months. On average, physicians estimated 24% (range, 2-44%) of patients with HAE were diagnosed with HAE-nC1INH, most of whom were adults (88%). To diagnose HAE-nC1INH, physicians most commonly assessed family history and plasma C4 levels (90% each), and C1 function and quantitative levels (87% each). On-demand and prophylactic treatment patterns varied widely across countries, with an average (range) of 56% (33-100%) of patients receiving on-demand treatment only, and 37% (0-67%) receiving both on-demand and prophylactic treatment. Physicians identified the greatest unmet needs in HAE-nC1INH management as treatment specifically indicated for this patient population and availability of an oral treatment. Conclusion: HAE-nC1INH may be more prevalent than previously reported. Importantly, our findings revealed varying diagnostic and treatment approaches. Validated, accessible diagnostic biomarkers and clinical outcomes derived from rigorous clinical trials assessing mechanistically based treatments would advance understanding and management of HAE-nC1INH.